Serra do Tabuleiro State Park and the water supply of Greater Florianópolis/SC - Pereira, Gabriel; Benini , Sandra Medina (Technical and Scientific Journal Green Cities, 2021)
The objective of this work is to raise questions and discuss the implications of urban and population growth in the legal Metropolitan Region of Florianópolis, for the water supply resources, as well as the relevance of the Serra do Tabuleiro State Park, located in the state of Santa Catarina, in this context. The methodology used in this work basically consists of a bibliographic survey, as well as the elaboration of a table to be presented. It was concluded that the park in question is vital for the preservation not only of animal and plant species, but also for the preservation of water resources, including springs, streams and rivers, which supply human populations in the Greater Florianópolis region. KEYWORDS: Serra do Tabuleiro. Florianopolis. Supply. Water resources.